2021
DOI: 10.3389/fcimb.2021.730222
|View full text |Cite
|
Sign up to set email alerts
|

Myrislignan Induces Redox Imbalance and Activates Autophagy in Toxoplasma gondii

Abstract: Toxoplasma gondii (T. gondii) is an important health problem in human and animals, and the highlighting side effects of launched therapeutic chemicals cannot be ignored. Thus, it is urgent to develop new drugs to against the infection. Myrislignan originated from nutmeg exhibited excellent anti-T. gondii activity in vitro and in vivo, and was able to destroy mitochondrial function. However, the exact mechanism of action is still unknown. In this study, combining RNAs deep-sequencing analysis and surface plasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In one study myrislignan originating from nutmeg induced a redox imbalance in T. gondii, which led to the autophagic killing of T. gondii (Zhang et al, 2021a). With respect to the underlying mechanisms, myrislignan can lower the mitochondrial membrane potential as well as ATP levels in T. gondii and disrupt mitochondrial function (Zhang et al, 2021a). In another study, Jili-Zhang et al found that licarin-B from nutmeg exhibits excellent anti-T. gondii activity by inducing mitochondrial swelling and nuclear disintegration (Zhang et al, 2021b).…”
Section: Facilitating Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study myrislignan originating from nutmeg induced a redox imbalance in T. gondii, which led to the autophagic killing of T. gondii (Zhang et al, 2021a). With respect to the underlying mechanisms, myrislignan can lower the mitochondrial membrane potential as well as ATP levels in T. gondii and disrupt mitochondrial function (Zhang et al, 2021a). In another study, Jili-Zhang et al found that licarin-B from nutmeg exhibits excellent anti-T. gondii activity by inducing mitochondrial swelling and nuclear disintegration (Zhang et al, 2021b).…”
Section: Facilitating Oxidative Stressmentioning
confidence: 99%
“…Methods to facilitate oxidative stress is worthy of future research. In one study myrislignan originating from nutmeg induced a redox imbalance in T. gondii , which led to the autophagic killing of T. gondii ( Zhang et al., 2021a ). With respect to the underlying mechanisms, myrislignan can lower the mitochondrial membrane potential as well as ATP levels in T. gondii and disrupt mitochondrial function ( Zhang et al., 2021a ).…”
Section: Promising Targets In Autophagy Pathway For T Gondi...mentioning
confidence: 99%
“…The results showed that, under normal circumstances, RHΔ ku80 tachyzoites contained well-organized organelles. By contrast, RHΔ ku80 tachyzoites were often deformed, vacuolized, and showed many autophagic vacuoles emerging in the cytoplasm after 3 hours of 10 −5 M progesterone treatment [ 22 ] ( Figure 3 c).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mitochondria are "little power stations", which are important organelles to supply energy to support the host cells. The mitochondrial electron transport chain (ETC) is an essential pathway for providing energy and participating in oxidation-reduction process of T. gondii (Zhang et al 2021). However, random disorders of mitochondria due to diabetes or other disadvantages can cause major disruption of metabolism that releases ROS (Tsuda et al 2018).…”
Section: Discussionmentioning
confidence: 99%